Phosphorus availability and legacy in highly weathered soils: unveiling the interplay with soil aggregation and carbon relationships across diverse agricultural land uses and integrated systems - Leite, Mauricio Cunha Almeida (2024)
Phosphorus (P) availability is a critical issue in tropical agriculture, particularly in highly weathered soils. Soil functions as a hierarchical, self-organizing, and emergent system, meaning land use can significantly influence P availability and its legacy through soil structure. This study investigates the impact of integrated agricultural systems (IAS), such as integrated crop-livestock-forestry (ICLF), on soil phosphorus cycling and structure. The first studyexamines how P lability correlates with soil structure, including water-stable aggregates (WSA), aggregate stability (AS), and maximum P adsorption capacity (Qmax), across three different textured Oxisols under various long-term conservative and non-conservative land uses. Results indicate that IAS maintained soil structure comparable to native vegetation (NV) in terms of large-WSA content and AS, unlike non-conservative land uses such as conventional tillage (CT). Micro-WSA emerged as the primary sink for total P across all sites and land uses. In IAS, Qmax decreased in micro-WSA, particularly under intensive land uses, but there was no significant pattern of increased non-labile P ratios compared with extensive grazing (EG) or NV, even after long-term phosphate fertilization. Principal component analysis showed that IAS, while highly correlated with total P and non-labile P, also closely correlates with soil structure parameters such as WSA and AS compared to CT. The second study highlights the importance of soil structure as an indicator of soil fertility and quality, affecting soil organic carbon (SOC), phosphorus lability as non-labile P (PNL), and the carbon-to-phosphorus ratio (C:P). Patterns of SOC and total phosphorus (PT) stocks were evaluated, along with the ratios of C:P, C: organic P (C:Porg), and C: non-labile P (C:PNL) in soil-water stable aggregates (WSA), is crucial for improving agricultural land use. Three Oxisols were evaluated concerning different agricultural land uses across large, macro, and micro-WSA soil aggregates and their aggregate stabilities (AS). Results showed that integrated systems (ICLF, ICL, ILF) generally had higher large-WSA proportions (40-45%) and significant SOC (50-60 Mg C ha-1) and P stock differences (40-50 kg P ha-1), particularly in large-WSA. NV consistently demonstrated the highest structural stability (50-52%) and enzymatic activities, with AcP reaching 30 µmol PNP g-1 soil h-1 and BG activities at 25 µmol MUF g-1 soil h-1. Integrated systems displayed high enzymatic activity and SOC, with notable variations in MBC (300-350 mg C kg-1) and MBP (50-70 mg P kg-1) across soil-WSA classes. SOC and P stocks were influenced by soil structure, with higher accumulations in micro-WSA. Micro-WSA retained more non-labile P, while large-WSA had more microbiological activity and higher C stock. This underscores the importance of maintaining good soil structure to enhance soil health, fertility, and nutrient stocks. Overall, the findings demonstrate the effectiveness of IAS in improving soil structure and nutrient dynamics, highlighting its potential in enhancing soil health and fertility, thus contributing to sustainable agricultural practices and food security.